VARIASI KANDUNAGN UAP AIR DI ATAS KOTOTABANG, SUMATERA BARAT HASIL ANALISIS DATA RADIO ACOUSTIC SOUNDING SYSTEM (RASS) SELAMA KEGIATAN CPEA-CAMPAIGN 2004 - Eddy Hermawan; Fikri Muhammad Abdul Wahab (Jurnal Sains Dirgantara, 2006)
As we know since June 2001, the National Institute of Aeronautics and Space (LAPAN) and Research Institute for Sustainable Humanosphere (RISH) of Kyoto University, Japan has already stared to make a joint research at LAPAN-Kototabang under the Coupling Processes Equatorial Atmosphere (CPEA) project. There are many research activities have already been dano by both institutes. One of them is the estimation of Total Precipitable Water (TPW) in the lower troposphere at Kototabang, West Sumatera (0.2˚S; 100.32˚E) during the CPEA I Campaign stared from April 10 to May 9, 2004 using many instruments. The main purpose of this paper is we would like to show how the TPW parameter can be estimated from the Radio Acoustic Sounding System (RASS) and radiometer and their correlation with the surface rainfall data. We applied the Wiesner (1970) technique when we estimated the TPW with specific humidity and air density taken from RASS and radiomater, respectively. Then, we analyzed the Cross-Correlation Function (CCF) when we compared the TPW and Optical Rain Gauge (ORG) data. In the same time, we analyzed the Boundary Layer Radar (BLR) data also to investigate the updraft and downdraft air mass activities from surface up to 5 km. We can see here the consistency of BLR, RASS and radiomater data when we investigated the vertical profile of water vapor over Kototabang. We found also a time variation of TPW, especially on April 24 and May 5, 2005 are about 0.43 and 0.35, respectively. Although both values look small relatively, but they are inough significant statistically.